Une raison qui incline, mais qui ne nécessite pas - Enrico Carontini (Communiquer)
This article presents the first of a three-part work concerning the three dimensions of communication : meaning, relation and the self-reference of meaning and relation. This reflection is drawn on the principle that the conditions necessary to communication require reference to a shared meaning which has been formed by and for the relation between participants of an interaction. The central concern of this first part is communication as it relates to the rational. To do so, emphasis is placed on the reference (the meaning) as based on Aristotle’s thought and Pierre Aubenque’s work. Communication can be conceived as a space of non-determinant mediation ; in other words, as a space of dialectical confrontation in which meaning is constructed and the result is a communicative reason (the reasonable).